Levels of nitrogenous substances and amino acids in bodies of Ross 308 hybrid cocks and hens over the course of rearing - E. Strakova; P. Suchy; P. Navratil; I. Herzig; M. Machacek (Veterinární Medicína, 2015)
Over the course of Ross 308 hybrid broiler chick cock and hen rearing, whole chicken bodies including feathers were monitored for changes in the levels of nitrogenous substances, essential amino acids (EAA) and non-essential amino acids (NEAA). At five-day intervals (Days 1, 5, 9, 15, 20, 26, 30, 35 and 40 of rearing), randomly selected chickens were slaughtered after 24 h of fasting. Over the course of rearing, N-substance levels ranged from 629.1 to 429.0 g/kg dry matter in hen bodies and from 616.0 to 477.3 g/kg dry matter in cock bodies. N-substance levels were statistically significantly different in the two sexes on rearing Days 35 and 40 (P ≤ 0.01). The levels of all amino acids (AA) in dry body matter of chickens up to 15 days of age dropped significantly over time, while in the period from Day 20 to Day 40, some AA levels increased or reached the baseline. With most AA, the levels were lower in hens than in cocks over the course of the trial. At the end of the trial (Days 35 and 40), statistically significant differences between the sexes were found for most EAA (P ≤ 0.01; P ≤ 0.05). NEAA, except for Ser and Ala, were also significantly higher in cocks on Days 35 and 40 (P ≤ 0.01; P ≤ 0.05). Among the monitored EAA, the dry matter of the bodies of hens exhibited the highest levels of Leu, 8.70% on average, followed by Val 6.54%, Lys 5.26%, Ile 5.25%, Thr 4.84%, Phe 4.30%, Tyr 2.51% and Met 2.21%. Leu was also the most abundant in the cock bodies, 8.42% on average, followed by Val 6.30%, Lys 5.36%, Ile 5.06%, Thr 4.57%, Phe 4.45%, Tyr 2.88% and Met 2.17%. Knowledge of the levels of nitrogenous substances, EAA and NEAA in the whole bodies of broiler chickens including feathers will help to determine optimal rearing conditions.